Examining implementation of health exception laws in six countries. - Fortman, Emily C.; Stratis, Catherine R.; Berchmans-Uwimana, Jean; Sepúlveda, Lilian; Chavkin, Wendy; Shaw, Dorothy; Awoonor-Williams, Koku (African Journal of Reproductive Health, 2026)
Exceptions to abortion restrictions on the grounds of protecting life or health enable essential care for pregnancy complications but are often underutilized or inconsistently applied. Through a narrative study, Global Doctors for Choice (GDC) aimed to identify barriers and facilitators to implementing these exceptions. We conducted literature and desk reviews and 15 semi-structured interviews (May-August 2025) with physicians, lawyers, and advocates from six countries: Colombia, Ghana, Ireland, Peru, Rwanda, and South Korea. Interviews were transcribed, de-identified, and analyzed for common themes. Implementation depended on disparate, often narrow or incorrect, interpretations by clinicians and institutions. Barriers included lack of training, geographic obstacles, personnel and supply constraints, stigma, and logistical delays, which push patients toward unsafe abortion. Facilitators involved comprehensive training with values clarification, patient awareness campaigns, unambiguous guidelines, and committed advocacy. Ultimately, clear legal frameworks, provider education, advocacy, and patient empowerment could improve access in diverse clinical and legal settings.